﻿﻿Mortality among African American women with sarcoidosis: data from the Black Women’s Health Study - ﻿Tukey, M.H.; ﻿﻿Berman, J.S.; ﻿Boggs, D.A.; White, L.F.; Rosenberg, L.; Cozier, Y.C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Background: Sarcoidosis is a chronic systemic granulomatous disease of unknown etiology that disproportionately affects black females.  Few studies have specifically addressed causes of death in this population. Objectives: To assess rates and causes of death among women with sarcoidosis in a prospective cohort study of U.S. black women. Design: The Black Women’s Health Study is a follow-up study of 59,000 U.S. black women aged 21-69 (median age 38) at entry in 1995.  Data on demographic and lifestyle factors and medical conditions, including sarcoidosis, were obtained through biennial questionnaires.  Deaths and causes of death from 1995 through 2009 among study subjects were identified from National Death Index data. We assessed mortality rates among women with and without a history of sarcoidosis.  Poisson regression models were used to estimate age-adjusted mortality rates. Cox proportional-hazards models were used to estimate hazard ratios for mortality and 95% confidence intervals. Results: A total of 121 deaths occurred among 1,192 women with a history of sarcoidosis and 2813 deaths among women without sarcoidosis.  Mortality was greater at every age among women with sarcoidosis and the overall multivariable-adjusted hazard ratio was 2.44 (95% CI 2.03-2.93, p